Pengaruh promosi, gaya hidup dan kemudahan penggunaan terhadap keputusan pembelian konsumen menggunakan jasa ShopeeFood pada Aplikasi Shopee - Al-Farabi, Muhammad Riza; Parhusip, Austin Alexander (ARKA INSTITUTE, 2022)
Purchasing decisions are consumer behavior, both individuals and households, in making final purchases in the form of products for personal consumption. The purpose of this study is to identify and analyze how promotions, lifestyles and ease of use influence purchasing decisions using ShopeeFood services on the Shopee application (Case study: students of the main potential university). The technique used in sampling is Random Sampling with a sample size of 152 respondents based on the Slovin formula and for data processing using SPSS.25. Based on the results of the analysis, it can be seen that the three variables used in this study have a positive and significant influence on purchasing decisions. It can be concluded that the variation of factors between the variables of promotion, lifestyle and ease of use together are able to explain the influence on purchasing decisions and the rest is explained by other variables that are not studied or outside the model.